Performance of New Rice Variety (Inpari 24) at Subak Amerta Nadi Kerta Village Payangan Sub-district of Gianyar Bali - Kariada, I Ketut; Aribawa, I. B. (KnE Life Sciences, 2017)
Model development of rice farming in the production centre area at Payangan Sub-district of Gianyar is designed to introduce a model called rice field laboratory. The principle of the model used is "build, operate and transfer (BOT), refering to a the disseminated model of innovation which is a large scale pilot model at the grass root level. The study introduced new varieties “Inpari”24 as an attempt to replace the old varieties that has lower productivity. Cultivation technology by implementing Legowo System 2: 1. The aim of this study was to determine the performance of new variety Inpari 24 in the cropping system in Subak Amerta Nadi, Kerta Village, Sub-district of Payangan Gianyar in the growing season 2014. This study used a randomized block design with two treatments of different cropping systems, namely: Legowo 2: 1 (40 x 20 x 10 cm) and tiles (20 x 20 cm), repeated 10 times. Variables observed in this study were: plant height, number of tillers, panicle length, number of grains per panicle and empty grains and yield per hectare. Data were analysed through analysis of variance, then followed by LSD test at 5% level. It was concluded that: (a) cropping systems significantly affected all variables of rice production, (b) the highest productivity was Legowo System which was 7.50 tons / ha, increased by 26.68% compared to tiles cropping system (the method used by farmers). Keywords: Inpari 24; planting system; rice